Motivation And Expectation Of Mona Gray In An Invisible Sign Movie (2011) Directed By Marilyn Agrelo: A Psychoanalytic Criticism - Wahyu, Wiwik Setyo, Drs. Abdillah Nugroho, M. Hum, Titis Setyabudi, S.S., M.Hum (2013)
The major problem of this research is to explain Motivation and Expectation of Mona Gray reflected in Marilyn Agrelo's An Invisible Sign movie. Objectives of this research are: to analyze the movie based on its structural elements, and to analyze movie based on A Psychoanalytic. This study is qualitative study. The object of the study is An Invisible Sign movie directed by Marilyn Agrelo published in 2011 in New York Production of iDeal Partners/ Silverwood Films. The data sources are divided into two namely primary data source and secondary data source. The primary data source is the film itself and the secondary data source is the other sources related to the analysis such as references, author's biography, criticisms relation to the problems and material related to the study whether picking up from books or internet. The methods of data collection are observation and library research. The technique of data analysis is descriptive analysis. This research comes to the following conclusions. First, based on the structural analysis of the movie, it shows that the character and characterization, setting, plot, point of view, theme, Mise-en-scene, cinematography, sound, and editing are related to each other and form the unity into good quality of a movie. Second, based on A Psychoanalysis theory, The analysis is started by analyzing Mona's Id, Ego, Superego, of her. For the last, the writer makes an analysis of Mona's Motivation and Expectation.